2019
DOI: 10.1167/iovs.19-27921
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Phenotypic and Genotypic Landscape of Nonsyndromic High Myopia: A Cross-Sectional Study in 731 Chinese Patients

Abstract: PURPOSE. High myopia (HM) is defined as a refractive error worse than À6.00 diopter (D). This study aims to update the phenotypic and genotypic landscape of nonsyndromic HM and to establish a biological link between the phenotypic traits and genetic deficiencies. METHODS. A cross-sectional study involving 731 participants varying in refractive error, axial length (AL), age, myopic retinopathy, and visual impairment. The phenotypic traits were analyzed by four ophthalmologists while mutational screening was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…The three-dimensional homology modeling of the candidate proteins was analyzed by using SwissProt and visualized with the PyMOL algorithm. Then, the pathogenicity of the identified causative mutations was predicted using multiple bioinformatics programs, including MutationTaster, Muta-tionAssessor, and SIFT, as described previously [68,69].…”
Section: Computational Assessment Of Mutation Pathogenicitymentioning
confidence: 99%
“…The three-dimensional homology modeling of the candidate proteins was analyzed by using SwissProt and visualized with the PyMOL algorithm. Then, the pathogenicity of the identified causative mutations was predicted using multiple bioinformatics programs, including MutationTaster, Muta-tionAssessor, and SIFT, as described previously [68,69].…”
Section: Computational Assessment Of Mutation Pathogenicitymentioning
confidence: 99%
“…Tran-Viet et al (2013) observed Sco2 protein localization in the retina, retinal pigment epithelium (RPE), and scleral wall in mouse ocular tissues. We further identified mutations A201P and I221V in SCO2 in 2019 (Cai et al, 2019c). Here, a new variant c.518A>T (p.D173V) in SCO2 is detected.…”
Section: Discussionmentioning
confidence: 78%
“…Up to now, only a few genes responsible for non-syndromic myopia have been discovered. In our previous study of large-scale screening of eight causative genes in 731 patients with HM, we merely identified mutations in 6.16% cases (Cai et al, 2019c). In this study, we identified four new candidate genes associated with HM.…”
Section: Discussionmentioning
confidence: 95%
“…11 Among Chinese adults 21 years of age and older, a 1-mm increase in axial length conferred a 10.84% higher risk of pathologic myopic retinopathy as well as a 7.35% higher risk of low vision. 55 Pathologic myopia is an important cause of low vision and blindness, especially in East Asia, where it is responsible for 12.2% to 31.25% of cases of low vision 11,56e59 and was ranked as the most frequent cause of blindness in one Chinese study (19.4%). 60 The Rotterdam Study found that myopic degeneration was the most common cause of visual impairment (25%) among those younger than 75 years of age in The Netherlands.…”
Section: Clinical Impact Of Myopiamentioning
confidence: 99%